Respuesta :
p+ 11 -4p= 8
⇒ (p -4p)+11= 8 (combine like terms)
⇒ -3p= 8-11
⇒ -3p= -3
⇒ p= -3/(-3)
⇒ p= 1
Final answer: p=1~
⇒ (p -4p)+11= 8 (combine like terms)
⇒ -3p= 8-11
⇒ -3p= -3
⇒ p= -3/(-3)
⇒ p= 1
Final answer: p=1~
Steps:
1) We have to keep the [tex]x[/tex]'s on one side. For simplification can only occur between [tex]x[/tex] with each other.
2) We have to keep the number on other side. Be careful that you do not simplify it with the [tex]x[/tex].
Simply, group the like terms and simplify.
Methods:
[tex]p+11–4p=8 [/tex]
=> [tex]p–4p+11=8 [/tex]
=> [tex]-3p+11=8[/tex]
=> [tex]-3p+11-11=8-11[/tex]
=> [tex]-3p=-3[/tex]
=> [tex]\frac{-3p}{-3}= \frac{-3}{-3} [/tex]
=> [tex]p=1[/tex]
1) We have to keep the [tex]x[/tex]'s on one side. For simplification can only occur between [tex]x[/tex] with each other.
2) We have to keep the number on other side. Be careful that you do not simplify it with the [tex]x[/tex].
Simply, group the like terms and simplify.
Methods:
[tex]p+11–4p=8 [/tex]
=> [tex]p–4p+11=8 [/tex]
=> [tex]-3p+11=8[/tex]
=> [tex]-3p+11-11=8-11[/tex]
=> [tex]-3p=-3[/tex]
=> [tex]\frac{-3p}{-3}= \frac{-3}{-3} [/tex]
=> [tex]p=1[/tex]